2010
DOI: 10.1016/j.molcel.2010.08.037
|View full text |Cite
|
Sign up to set email alerts
|

CK2 Phospho-Dependent Binding of R2TP Complex to TEL2 Is Essential for mTOR and SMG1 Stability

Abstract: TEL2 interacts with and is essential for the stability of all phosphatidylinositol 3-kinase-related kinases (PIKKs), but its mechanism of action remains unclear. Here, we show that TEL2 is constitutively phosphorylated on conserved serines 487 and 491 by casein kinase 2 (CK2). Proteomic analyses establish that the CK2 phosphosite of TEL2 confers binding to the R2TP/prefoldin-like complex, which possesses chaperon/prefoldin activities required during protein complex assembly. The PIH1D1 subunit of the R2TP comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
162
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(178 citation statements)
references
References 29 publications
4
162
0
Order By: Relevance
“…Proteomic experiments in Schneider S2 cells showed that dTOR interacts with Pontin, Reptin, Spag, and liquid facet-related, a distant homolog of Tel2 (31,34). In mammalian cells, recruitment of the whole R2TP by Tel2 is necessary to stabilize mammalian TOR (7). Taken together, these data support the conservation of R2TP in the stabilization and assembly of PIKK complexes.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Proteomic experiments in Schneider S2 cells showed that dTOR interacts with Pontin, Reptin, Spag, and liquid facet-related, a distant homolog of Tel2 (31,34). In mammalian cells, recruitment of the whole R2TP by Tel2 is necessary to stabilize mammalian TOR (7). Taken together, these data support the conservation of R2TP in the stabilization and assembly of PIKK complexes.…”
Section: Discussionsupporting
confidence: 64%
“…Later on, we showed that the R2TP is also involved in the early cytoplasmic steps of RNA polymerase II biogenesis (6). Finally, mammalian R2TP also stabilizes proteins from the PI3 kinase-like kinase family (PIKKs), including mammalian TOR and SMG-1, two regulators of protein synthesis (7). This function in PIKK stabilization is dependent on an adaptor called Tel2 (7).…”
Section: Rpap3mentioning
confidence: 99%
See 2 more Smart Citations
“…Rvb1 and Rvb2 are two highly conserved AAAϩ helicases involved in many different critical complexes in the cell (3,4). The R2TP complex is highly conserved from yeast to mammalian cells and has been shown to be required for the proper assembly of box C/D small nucleolar ribonucleoproteins (5,2), for the assembly of RNA polymerase II (6,7), and for the stability of the phosphatidylinositol 3-kinase-related kinases through binding to TEL2 (8). Furthermore, both human Pih1 (PIH1D1) and human Tah1 (RPAP3) have been shown to regulate apoptosis (9,10).…”
mentioning
confidence: 99%